Neonatal calf mortality in dairy animals and strategies for improvement - Singh, Rakesh Kumar; Tripathi, A K (Indian Farming, 2017)
Most important aspect of successful dairy is to control calf mortality to make it profitable industry. Up till now many researches have been conducted to study the different causes of calf mortality so that these causes can be minimized and economic losses are minimal. For a profitable dairy business biosecurity measures, prophylactic measures and nutrition should be a part of dairy management. Early calf mortality not only decreases the milk and meat production, but also lowers genetic reservoirs by creating problems in breeding programs. Still there is need to investigate the improved measure for control of early calf mortality, particularly considering the practices of dairy industry of India.